(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research paper aims to investigate the effectiveness of assertiveness training in enhancingself-esteem among B.Sc nursing students. Self-esteem plays a vital role in the personal and professionaldevelopment of nursing students, as it influences their confidence, communication skills, and overall wellbeing.However, limited research has focused on the specific impact of assertiveness training on selfesteemwithin the context of nursing education. The research methodology is the backbone of everystudy. It’s the foundation of the whole investigation. The effects of assertiveness training onteenagers’ sense of self-worth were investigated. Adolescents who were enrolled in and metinclusion requirements at Higher Secondary Schools in either Karnataka or Uttar Pradesh. Thesample size is 60 B.Sc. nursing students. Evaluation of the study’s success is the focus of thissection, which details the sampling strategy, data analysis, and interpretation. Following is adescription and tabulation of the information gathered